Desain Bahan Belajar Elektronik Berbasis Higher Order Thinking Skill (HOTs) pada Mata Kuliah Kapita Selekta Hasil Penelitian - Mohammad Muhyidin Nurzaelani; Mita Septiani; Maimunah Maimunah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
21st-century education requires a transformation in learning to provide students who can meet challenges by applying higher order thinking skills (HOTs). This study aims to produce an electronic learning material design based on higher order thinking skills (HOTs) appropriate to the Kapita Selekta Research Results (KSHP) course. This research uses the development research method by adopting the Rowntree model. Data collection is carried out by studying documentation and distributing questionnaires to students who will take the KSHP course in odd semester 2020. This research resulted in a design of electronic learning materials based on HOTs, which then required the next stage of development, implementation, and evaluation of these learning materials to be ready to use in order to facilitate student learning in the KSHP course.